Nutcracker phenomenon secondary to superior mesenteric artery syndrome. Issue 1 (19th January 2023) - Pacheco, Tulio Brasileiro Silva; Chacon, Andre Camara Matoso; Brite, Jasmine; Sohail, Amir H; Gangwani, Manesh Kumar; Malgor, Rafael D; Levine, Jun; Amaral Gurgel, Gutenberg do
Abstract: Superior mesenteric artery (SMA) syndrome, compression of the duodenum due to a decreased angle between the aorta and SMA, has a wide range of clinical presentations making it difficult to diagnose. Compression of the left renal vein is known as Nutcracker syndrome. We present the case of a 26-year-old male with a delayed diagnosis of SMA syndrome and Nutcracker phenomenon due to the patient's history of chronic pancreatitis. As a result of his obstruction and aspiration pneumonia, he was diagnosed with septic shock. The patient was treated for septic shock and maintained on an enteric diet with improvement in the body mass index and complete resolution of SMA syndrome symptoms.